PENGGUNAAN DEIKSIS DALAM KUMPULAN CERITA RAKYAT ROKAN HULU - Apraini. P '; Auzar '; Hasnah Faizah AR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study, entitled the use of Deiksis in the collection of the folklore of Rokan Hulu. The purpose of this study is to describe the various deiksis contained in a batch of Rokan Hulu folklore. The research method used was qualitative data describing methods, descriptive. Furthermore, there are four kinds of deiksis used in the collection of the folklore of Rokan Hulu, which consists of deiksis place, deiksis time, deiksis, and deiksis persona. Based on penenelitian about the use of Deiksis in the collection of the folklore of Rokan Hulu, then the number of data deiksis found sebayak 200 deiksis data, the most frequently used is deiksis with 142 persona data. On the order of second place with 50 deiksis data. In the third sequence deiksis time with the amount of data that found as many as 47 data, and subsequent social deiksis with the amount of data 18.Key Word: Deiksis, Story of the folklore